Investigation of blast resistance genes in a broad-spectrum resistant indigenous rice, Yang Mawng variety - Suksiri, W.; Parinthawong, N. (International Journal of Agricultural Technology, 2020)
The indigenous rice Yang Mawng variety was highly resistant to 24 isolates and moderate resistant to 3 isolates of P. oryzae. The results confirmed the broad-spectrum resistance to blast disease of Yang Mawng variety. The pathogenicity test of 27 isolates of P. oryzae was conducted on 31 Near Isogenic Lines (NILs). The result showed that virulence index (VI) was valued from 0 to 0.50 and the most pathogenic isolate on NILs was UBN2010 13515. The investigation for 8 rice blast disease resistance genes of Yang Mawng variety was done using blast resistance gene specific primers and PCR technique. The result showed that 5 blast resistance genes including Pi9, Pigm(t), Pi54, Pib and Pita, were detectable. The information of this research is a preliminary data for study of resistance genes present in Yang Mawng variety.